THE INFLUENCE OF TAXPAYER AWARENESS, TAX SANCTIONS, AND LEVEL OF EDUCATION ON INDIVIDUAL TAXPAYER COMPLIANCE - Putu Amanda Wedayanti; I Nyoman Wijana Asmara Putra (Adisam Publisher, 2025)
Individual Taxpayer Compliance is an individual taxpayer's compliance with the tax provisions required by legal regulations. This research aims to analyze the influence of taxpayer awareness, tax sanctions, and level of education on individual taxpayer compliance at KPP Pratama Tabanan. The sample determination method used is a non-probability sampling method with a purposive sampling technique and questions distributed online via the Google Form platform. The population used in this research is all individual taxpayers who are registered as mandatory SPT at KPP Pratama Tabanan, totaling 222,491. Based on the Slovin formula calculation, a sample of 100 respondents was obtained who were Individual Taxpayers registered at KPP Pratama Tabanan. Hypothesis testing used in this research uses multiple linear regression analysis which is processed based on the Statistical Program for Social Science (SPSS) application version 25. The results of the research show that taxpayer awareness, tax sanctions, and level of education have a positive and significant effect on individual taxpayer compliance. Personal.